The impact of ChatGPT on journalism : social listening, bibliographic production, and media agenda - Sidorenko Bautista, Pavel; Cabezas Clavijo, Álvaro; Cantón Correa, Javier; Alba Ruiz, Rubén (BiD (Barcelona, Spain), 2024)
Objective: Considering the powerful emergence of ChatGPT in society at large and in journalism in particular, this study aims to quantify the impact of ChatGPT on journalism from the perspective of news generation on this topic, its repercussions on social networks, and its impact on the academic sphere. -- Methodology: This study quantitatively analyses the impact of ChatGPT on journalism from its launch on 30 November 2022 to 18 November 2023. It examines news coverage, Wikipedia visits, social media posts (Facebook, Instagram, and X), and academic output. Data was collected from Media Cloud, Wikipedia, and Proquest. -- Results were generated in Flourish Studio, and analysis included normalization of records to avoid duplicates and ensure relevance to scholarly output. Results: The analysis of diverse documents underscores the versatility of the technology and the growing intersection between automation and journalistic writing. The study anticipates a future of increased human-machine collaboration in journalism. Key findings indicate widespread global coverage of the topic, reflecting a commensurate audience interest, as evidenced by internet search logs and social conversations.